Números primos Gaussianos para o ensino médio - Almeida, Cybele Verde Aragão de (2014)
Our purpose in this study is to present a special category of numbers as follows: Gauss' prime Numbers . We take a historical approach on how the Carl Friesrich Gauss' interest in the study of complex numbers emerged and as a result Gauss' integers have been develop in his tribute of respect. we mention the most important and /or interesting theorems with their propositions as well as their respective demonstrations in which we have developed some examples to make it easier to understand. Gaussian prime numbers will also be displayed and we will conclude with activities for the high school involving basic concepts of complex numbers ,and comparisons between integer Prime Numbers and Gaussian prime Numbers, involving the Fundamental Theorem of Arithmetic.